Analysis of Indonesia's National Interest in Cooperation with South Korea for the Development of KFX/IFX Fighter Aircraft (2008-2023) - Ismiyatun, Ismiyatun; Pramudhipta, Adhytya Bagus (Maneggio, 2025)
This study aims to analyze the KFX/IFX fighter development cooperation between Indonesia and South Korea in the period 2008-2023. This study uses qualitative methods with a literature study approach to understand the factors behind Indonesia's decision in this cooperation. The framework used is Donald E's theory of national interest. Nuechterlein, which covers four main aspects: defense interests, economics, ideology, and international order. The results showed that Indonesia chose to be involved in the development of kfx/IFX fighter aircraft because it was considered more profitable than the option to purchase aircraft from other countries. In terms of defense, this cooperation aims to improve the technological capabilities of the national defense equipment. Economically, the project supports the strengthening of the domestic aerospace industry and technology transfer. From the ideological aspect, this cooperation is in line with the principle of non-active foreign policy. Meanwhile, in the context of International Governance, Indonesia's involvement in this project reflects its efforts in strengthening its strategic position in the global arena. Thus, this cooperation not only has an impact on defense modernization, but also supports Indonesia's economic development and Diplomacy at the international level.